High prevalence of curable sexually transmitted infections among pregnant women in a rural county hospital in Kilifi, Kenya. - Masha, S; Wahome, E; Vaneechoutte, M; Cools, P; Crucitti, T; Sanders, E (Public Library of Science, 2017)
BACKGROUND: Women attending antenatal care (ANC) in resource-limited countries are frequently screened for syphilis and HIV, but rarely for other sexually transmitted infections (STIs). We assessed the prevalence of curable STIs, defined as infection with either Chlamydia trachomatis or Neisseria gonorrhoeae or Trichomonas vaginalis, from July to September 2015. METHODS: In a cross-sectional study, women attending ANC at the Kilifi County Hospital, Kenya, had a urine sample tested for C. trachomatis/N. gonorrhoeae by GeneXpert® and a vaginal swab for T. vaginalis by culture. Bacterial vaginosis (BV) was defined as a Nugent score of 7-10 of the Gram stain of a vaginal smear in combination with self-reported vaginal discharge. Genital ulcers were observed during collection of vaginal swabs. All women responded to questions on socio-demographics and sexual health and clinical symptoms of STIs. Predictors for curable STIs were assessed in multivariable logistic regression. RESULTS: A total of 42/202 (20.8%, 95% confidence interval (CI):15.4-27.0) women had a curable STI. The prevalence was 14.9% for C. trachomatis (95% CI:10.2-20.5), 1.0% for N. gonorrhoeae (95% CI: 0.1-3.5), 7.4% for T. vaginalis (95% CI:4.2-12.0), 19.3% for BV (95% CI: 14.1-25.4) and 2.5% for genital ulcers (95% CI: 0.8-5.7). Predictors for infection with curable STIs included women with a genital ulcer (adjusted odds ratio (AOR) = 35.0, 95% CI: 2.7-461.6) compared to women without a genital ulcer, women who used water for cleaning after visiting the toilet compared to those who used toilet paper or other solid means (AOR = 4.1, 95% CI:1.5-11.3), women who reported having sexual debut ≤ 17 years compared to women having sexual debut ≥18 years (AOR = 2.7, 95% CI:1.1-6.6), and BV-positive women (AOR = 2.7, 95% CI:1.1-6.6) compared to BV-negative women. CONCLUSION: One in five women attending ANC had a curable STI. These infections were associated with genital ulcers, hygiene practices, early sexual debut and bacterial vaginosis.